Microflora communities which can convert digested sludge to biogas. Issue 15 (3rd July 2022) - Kon, Ayaka; Omata, Shunsuke; Hayakawa, Yuhei; Aburai, Nobuhiro; Fujii, Katsuhiko
ABSTRACT: In the present study, we developed several microflora communities that utilize digested sludge (DS), the recalcitrant waste product of anaerobic digestion, as a substrate for biogas production with the aim of their future application to DS recycling. Strict enrichment with DS as the sole nutrient source was introduced to culture microbes from soil and herbivore dung samples; microflora communities promoting stable levels of biogas production were obtained. The average methane and hydrogen yield from soil-derived microflora were 4.86 and 0.94 ml per 1.0 g DS, respectively. Notably, two microflora communities enriched from a riverbank sediment produced 20.79 ml and 14.10 ml methane from 1.0 g DS. By contrast, the methane and hydrogen yield for herbivore dung-derived microfloras were on average 1.31 ml and 1.87 ml per 1.0 g DS, respectively. Potent hydrogen-biogas producers were obtained from rabbit (4.12 ml per 1.0 g DS), goat (3.16 ml per 1.0 g DS), and sheep dung (2.52 ml per 1.0 g DS). The cultured microflora communities included representatives from the eubacterial genera, Clostridiaceae and Eubacteriaceae together with several anaerobic genera. Pseudomonas spp. are found in the riverbank sediment-derived microfloras, suggesting that the floras employ syntrophic acetate oxidation and hydrogentrophic methanogenesis (SAO-HM) pathway for methane production. The methanogenic microflora communities were dominated by bacteria from the Methanobacteriaceae family and unclassified archaea. Moreover, ascomycetous fungi and protists were found, implying that they act as oxygen scavengers and bacterial grazers, respectively. Enzymatic analysis suggested that the microfloras hydrolyze DS via cellulase, chitinase, and protease activities. GRAPHICAL ABSTRACT: